Removal of copper from wastewater by agricultural waste wheat bran - Singh K.K.; Singh N.L.; Hasan S.H. (My University, 2025)
Wheat bran a low cost biosorbent has been used for the removal of Copper (II) from wastewater. The effect of various parameters, such as contact time, adsorbate concentration, pH of the medium and temperature have been studied. The conditions for the optimum removal of copper (II) were found 94% at pH of 8.0, initial concentration, 40 mg/L and temperature 20°C. Dynamics of the sorption process were studied and the values of rate constant of adsorption pore diffusion coefficient and mass transfer coefficients were calculated. A generalised empirical model is proposed for the kinetics at different initial concentrations. Mass transfer of Cu (II) from the bulk to the solid phase, namely wheat bran has also been studied at different temperatures. Different thermodynamic parameters, namely, changes in standard free energy, enthalpy and entropy have also been evaluated and it has been found that the reaction was spontaneous and exothermic in nature. The applicability of Langmuir isotherm suggests the formation of monolayer coverage of adsorbate on the surface of the adsorbent. The data has been subjected to multiple regression analysis and a computer model has been developed to predict the removal of Cu (II) from wastewater. © 2004 - Kalpana Corporation.